Effects of Preexisting Psychotropic Medication Use on a Cohort of Patients with Ischemic Stroke Outcome. (22nd September 2020) - Jun-O'Connell, Adalia H.; Jayaraman, Dilip K.; Henninger, Nils; Silver, Brian; Moonis, Majaz; Rothschild, Anthony J.
Abstract : Background . Several studies investigated the use of selective serotonin reuptake inhibitors (SSRI) after ischemic stroke to improve motor recovery. However, little is known about the effects of preexisting psychotropic medication use (PPMU), such as antidepressants, on a long-term ischemic stroke functional disability. Objective . We sought to determine the prevalence of PPMU and whether PPMU relates to the long-term clinical outcome in a cohort of patients presenting with acute ischemic strokes. Methods . We retrospectively analyzed 323 consecutive patients who presented with an acute ischemic stroke in a single institution between January 2015 and December 2017. Baseline characteristics, functional disability as measured by the modified Rankin Scale (mRS), and major adverse cardiovascular complications (MACE) within 365 days were recorded. The comparison groups included a control group of ischemic stroke patients who were not on psychotropic medications before and after the index ischemic stroke and a second group of poststroke psychotropic medication use (PoMU), which consisted of patients started on psychotropic medication during the index admission. Results . The prevalence of PPMU in the studied cohort was 21.4% (69/323). There was a greater proportion of females in the PPMU than in the comparison groups (P < 0.001 ), while vascular risk factors were similar in all groups, except for an increased presence of posterior circulation infarcts in the PPMU (37.4% vs. 18.8%, P < 0.001 ). Among the patients with available 1-year follow-up data (n = 246 ), we noted significantly greater improvement in stroke deficits, measured by National Institute of Health Stroke Scale (NIHSS) between PPMU and PoMU vs. control (3 (0-7) versus 1 (0-4), P = 0.041 ). The 1-year mRS was worse in PPMU and PoMU compared to the control group (2 (IQ 1-3) vs. 2 (IQ 0-3) vs. 1 (IQ 0-2), respectively, P = 0.013 ), but delta mRS reflecting the degree of mRS improvement showed no significant difference between any PMU and control patients (P = 0.76 ). There was no statistically significant difference in MACE. Conclusion . PPMU in ischemic stroke is common; it can be beneficial in ischemic stroke in the long-term clinical outcome and is not associated with increased risks of MACE.